The hunt for dark infinity - Dashner, James, 1972- (Dashner, James, 1972- 13th reality, 2009)
After being kidnapped by Mr. Chu, Atticus "Tick" Higginbottom and his friends Paul and Sofia must survive a series of tests in several different Realities.